Rancangan Perbaikan Penilaian Tutorial Berdasarkan Sudut Pandang Tutor dan Mahasiswa serta Literatur - Fuad Khadafianto; Gandes Retno Rahayu; Efrayim Suryadi (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2016)
Background: Problem Based Learning (PBL), a form of active learning model that is constructive, independent, collaborative and contextual, implemented in the learning process in the form of tutorial discussions. The quality of tutorial discussion need to be improved. One way to improve the quality of the tutorial is to revise or to select the appropriate assessment methods of tutorial discussion. Aside from tutor perception as a user, student perception about the benefits of the assessment process in PBL as subjects assessed need to be considered as a consideration in determining the appropriate model of assessment. One of tutorial discussion PBL method is using a seven jumps. This tutorial process is assessed and the result becomes a component of summative assessment. Therefore, the quality of these assessments must be guaranteed in terms of validity, reliability, impact of learning and in terms of ease of implementation.Method: This study used a qualitative method through a case study approach that use focus group discussions and in-depth interviews. This research carried out in the faculty of medicine of Islamic University of Indonesia. The study population was representative students of the years 2011-2014, the representative of tutors, and the leadership of the study program and faculty. Results: there were eight categories of perception in the tutorial discussion assessment. The perceptions included the perception of tutor and student knowledge about the assessment tutorials, the conformity tutorial discussion assessment with the concept of PBL, the technical assessment, the deviation judgment, the assessment objectivity, the assessment impact of the tutorial process, the learning/educational impact of tutorials assessment, and the recommendation of tutorial assessmentConclusion: Based on eight categories of perception in the tutorial discussion assessment, this study recommended three things, recommendation to keep doing the assessment of tutorial, to improve the objectivity of ratings tutorial by improving various components related to the assessment of tutorials, and to prevent the occurrence of irregularities in tutorial assessment.